MEANING OF BANK SECRETS AFTER THE ENACMENT OF LAW NUMBER 9 OF 2017 ON STIPULATION OF GOVERNMENT REGULATION IN LIEU OF LAW NO. 1 OF 2017 ON ACCESS TO FINANCIAL INFORMATION FOR THE INTERESTS TAXATION INTO LAW - Jamilatus Sholihah; Dyah Ochtorina Susanti; Ermanto Fahamsyah (Warmadewa Press, 2018)
Abstract The national economic development in Indonesia is inseparable from the banking role. The existence of the stipulation of Government Regulation in Lieu of Law (PERPU) Number 1 of 2017 on Access to Financial Information for Tax Purposes will certainly affect the regulation of the banking sector in particular related to bank secrets. The establishment of the Perpu appears to have attracted the attention of the government to immediately pass it into law. It is proven which on 23 August 2017 President Joko Widodo has authorized the Perpu to become a law through Law Number 9 of 2017 on Stipulation of Government Regulation in Lieu of Law (PERPPU) Number 1 of 2017 on Access to Financial Information for Tax Purposes into the Law -What. The policy is a form of Indonesia's commitment to participate in the automatic exchange of information globally for tax purposes. The automatic opening of bank secrets for tax purposes will certainly affect the previous banking arrangements, especially those related to bank secrets. Therefore, in order to avoid overlapping arrangements, the state of Indonesia needs to harmonize all regulations relating to bank secrets and the opening of bank secrets for tax purposes. Keyword: Banking Secrecy, Taxation.